Monitoring of strength, inflammation and muscle function in allogenic stem-cell transplantation patients – a pilot study for novel biomarker and risk stratification determination - Schulz, Sebastian Viktor Waldemar; Bizjak, Daniel Alexander; Moebes, Elena; John, Lucas; Wais, Verena; Bunjes, Donald; Sala, Elisa; Steinacker, Jürgen Michael; Kirsten, Johannes (Frontiers in Immunology, 2023)
Background: Low aerobic capacity is associated with an increased mortality risk in allogenic stem-cell transplantation (alloSCT) patients, but currently used risk scores in the pre-transplantation workup are still underestimating physical activity as a prognostic factor. Aim: To examine the physical condition, muscle function, blood inflammation and training adherence of alloSCT patients during inpatient time to identify potential biomarkers associated with development of myopathy and sarcopenia. Methods: Patients undergoing alloSCT were examined at four time points (T0: before alloSCT; Tha: hospital admission; T1: engraftment; T2: inpatient discharge). T0 included cardiopulmonary performance, body composition, grip and knee strength, motor skill tests (One-leg stand/Tinetti/Chair-rising), blood sampling (blood cell profiling and inflammation targets (Kynurenin/high sensitivity C-reactive Protein (hsCRP)/Tumor necrosis factor alpha (TNF-alpha)/Musclin/Galectin-3) and quality of life, state of health, fatigue, muscle weakness and physical activity by questionnaires (IPAQ/BSA/SARC-F/Fatigue). At T1 and T2, blood samples, grip strength and motor skill tests were repeated. Glucocorticoid dose and daily physical activity were documented during inpatient stay. Results: 26 of 35 included patients (4 females; age 55.58±12.32 years; BMI 24.70±3.27 kg/m2; VO2peak 16.55±4.06 ml/min/kg) could proceed to alloSCT. Grip strength and Tinetti decreased from T0 until T2, no difference in Chair-rising test, One-leg and Tandem stand. All patients engrafted after 24.9 days±3.9 days. HsCRP and Kynurenine increased from T0 to T1, decreased at T2. TNF-alpha (T0vsT2/T1vsT2) and Musclin (T0vsT1) decreased. At T2, Galectin-3 was higher compared to T0/T1. Correlation analysis of grip strength and inflammatory markers revealed a positive correlation with TNF-alpha at T2. 50% of patients documented physical activity and questionnaire and reported a 50%-reduction of daily endurance and strength training between T1 to T2. Conclusion: Allogeneic stem-cell transplantation is associated with immune system vulnerability due to conditioning, increased inflammation and fatigue, and loss of muscle strength and function. In addition to hsCRP, Kynurenine seems to be a reliable biomarker to monitor acute and regenerative inflammation status of alloSCT patients, while Musclin and Galectin-3 may be added to physiological assessment regarding myopathy and sarcopenia. Grip strength and daily activity level should be documented by professionals to identify risk patients early and support them with optimal (exercise) therapy.